137k views
2 votes
Giselle solved the quadratic equation x^2+5x-6=0 by factoring. Her work shown below. In which step did she first make a mistake? Find the correct answer. Step 1: x^2+5x-6=0 Step 2: (x+2)(x+3)=0 Step 3: x+2=0, x+3=0 Step 4: x=-2 or x=-3 Step 5: {-2,-3}

User Colemars
by
4.8k points

1 Answer

5 votes

x = - 6 or, 1

Explanation:

The given quadratic equation:


x^2+5x-6=0

By factorisation mmethod,


x^2+6x-x-6=0

⇒ x(x + 6) - 1(x + 6) = 0

⇒ (x + 6)(x - 1) = 0

⇒ x + 6 = 0 or, x - 1 = 0

⇒ x + 6 = 0 ⇒ x = - 6

⇒ x - 1 = 0 ⇒ x = 1

∴ x = - 6 or, 1

User Juandesant
by
5.0k points